33‐1: Invited Paper: Tabletop True 3D Display Systems based on Projection Light Field and Integral Imaging. Issue 1 (25th September 2020) - Wang, Qiong-Hua; Li, Hai-Feng; Xia, Yun-Peng; Li, Shuang; Ren, Hui; Ni, Li-Xia
Abstract : In this paper, we introduce two tabletop true 3D display systems based on the projection light field and integral imaging. In the projection light field tabletop system, a dual‐panoramic camera is used for multi‐face real time tracking and achieving full parallax, and gesture‐based interaction by Leap Motion is also added for free and accurate interaction. In the integral imaging system, an optimized compound lens array is designed to improve the viewing angle of the 3D image, and the liquid light diffuser is proposed to increase the depth of field of the 3D image.